Comparison of Islamic Education in Indonesia and Thailand - purnomo, Dedi; Pane, Ismail (Rumah Riset Publisher, 2023)
This study aims to determine the Islamic education system in Indonesia and Thailand. Islamic education written in Indonesia is growing very fast compared to Southeast Asian countries. The number of madrassas and farmers proves it. Islamic education in Indonesian is one of the compulsory subjects in public schools and universities. In Thailand, a country where the majority adheres to Buddhism is 10%. The Muslim population of the entire population of Thailand. With that amount. The education of minority Muslims in Thailand also has something in common. Islamic Education in Indonesia. There are also pesantren in Thailand and madrasas whose education system is not far from Indonesia. The only difference is in quantity. Subjects examined in national exams and compulsory to study Thai there.